THE ROLE OF SINDHIND ZIJ AS THE FIRST ISLAMIC ASTRONOMICAL CALCULATION TABLE IN INDIAN CIVILIZATION - Faizah, Nur; Binti Roslan, Nura'zirah (Fakultas Syari'ah dan Hukum UIN Walisongo, 2023)
Astronomy has developed in India since prehistoric times. However, astronomy’s first work appeared during the Vedanga Jyotisa era, written by Lagadha, the oldest literary book in India. Using qualitative methods with a library research approach, it was found that Indian astronomers researched Astronomy and wrote books. One of the books that first made Muslim scientists interested in the world of astronomy was the book Brāhmasphuṭasiddhānta, which was translated into Arabic by Al-Fazari (d. 796 AD) during the Caliphate of Al-Manṣūr from the Abbasid dynasty. Al-Fazari (d. 796 AD) became the first Muslim astronomer to compile Zij, with his calculations converted into the Hijri Calendar. After Al-Fazari (d. 796 AD) collected this Zij, other Zijs were born, which became the forerunners for the composition of the epimeris and other counts. Around the beginning of the 11th century, Al-Biruni (973-1048 AD) spread da'wah to India and introduced the study of Islamic astronomy in India.